Use of biomarkers in early cancer detection: A literature review (Research, Society and Development, 2024)
Introduction: Biomarkers emerge as fundamental tools in oncological diagnosis. Measurable biological characteristics, they indicate normal, pathological biological processes or responses to therapies. In oncology, they are used for early detection of cancer, prognosis, prediction of response to treatment and monitoring of disease progression. The introduction highlights the importance of early cancer detection and the relevance of biomarkers for effective interventions. Genomic, proteomic, metabolomic and epigenetic biomarkers are essential to detect early molecular and cellular changes. Objective: This article aims to provide a comprehensive overview of the crucial role of biomarkers in early cancer detection, highlighting technological advances, challenges faced and clinical implications for improving patient outcomes. The methodology includes an integrative literature review, using databases such as PubMed, Scopus and Web of Science to identify relevant studies. Search terms included “biomarkers,” “early cancer detection,” and “diagnostic technologies.” Articles were selected using strict inclusion and exclusion criteria, and data extracted and analyzed to identify trends and advances in the field. This article reviews the role of biomarkers in the early detection of cancer, addressing their importance, detection methodologies, technical challenges and impacts on patient survival and prognosis. Results: The use of genomic, proteomic, metabolomic and epigenetic biomarkers demonstrates great potential for identifying early molecular and cellular changes, enabling faster and more effective interventions. However, tumor heterogeneity, outcome variability, clinical validation, and complexity of data interpretation remain significant challenges that need to be overcome.